Some multivariable Gaussian hypergeometric extensions of the Preece theorem - Qureshi, M. I.; Sadiq Khan, M.; Pathan, M. A.; Khan, N. U. (The ANZIAM journal, 2006)
Some generalisations of the Preece theorem involving the product of two Kummer's functions 1F1 are obtained using Dixon's theorem and some well-known identities. Its special cases yield various new transformations and reduction formulae involving Pathan's quadruple hypergeometric function and Srivastava's quadruple hypergeometric function F(4) and triple hypergeometric function F(3). Some known results of Preece, Pathan and Bailey are also obtained as special cases.